Fatigue Experience and Coping Strategies among Cancer Patients Receiving Chemotherapy - Dahal, Anika; Meheta, Raj Kumar (Journal of Nepal Health Research Council, 2018)
Background: Cancer is considered one of the foremost common causes of death. Fatigue is among the distressing symptoms for cancer patients receiving chemotherapy. Adequate coping is essential for individual to deal with the effects of cancer related treatment. The objective of the study was to find out the fatigue experience and coping strategies among cancer patients receiving chemotherapy. Methods: A descriptive, cross-sectional research design was used for the study. The samples was taken from day care and medical oncology ward of BP Koirala Memorial Cancer Hospital, Bharatpur. A total of 120 cancer patients receiving chemotherapy of 18 years and above were selected by using non probability consecutive sampling technique. Data was collected by using standard tool, Fatigue Symptom Inventory and Brief Cope. Data analysis was done by descriptive and inferential statistics. Results: The study revealed that 82.5% of respondents had experienced fatigue and 50.8% respondents had used adequate coping strategies where “self distraction”(2.76±1.02) was the most used coping strategy by the respondents. Fatigue experience and coping strategies had negative correlation (r=-0.490, p=<0.001). Conclusions: Majority of the respondents had experienced fatigue, and half of the respondents used adequate coping strategies. The different methods of coping strategies for fatigue and chemotherapy related effects should be expanded as per the best available evidence to lower fatigue and other adverse effects.